Faith in the fight: religion and the American solider in the great war - Ebel, Jonathan H. (Princeton University Press, 2010)
Faith in the Fight tells a story of religion, soldiering, suffering, and death in the Great War. Recovering the thoughts and experiences of American troops, nurses, and aid workers through their letters, diaries, and memoirs, Jonathan Ebel describes how religion--primarily Christianity--encouraged these young men and women to fight and die, sustained them through war's chaos, and shaped their responses to the war's aftermath. The book reveals the surprising frequency with which Americans who fought viewed the war as a religious challenge that could lead to individual and national redemption